Isle of Man : Financial Sector Assessment Program Update; Detailed Assessment of Observance of the Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2009)
This paper presents a Detailed Assessment of the Isle of Man's (IOM) observance of the Insurance Core Principles. Regulation has been strengthened since the 2003 Offshore Financial Center assessment. The Insurance and Pension Authority has been putting in place Memorandums of Understanding with home regulators and is exchanging information extensively. After rapid growth in 2005 and 2006, new business volumes and investment performance have been adversely affected by weaker global equity markets. The number of captives established in the IOM has fallen, reflecting competition from jurisdictions within the European Union.